Pengolahan Limbah Sayur Kol menjadi Pupuk Kompos dengan Metode Takakura - Nurdini, Lulu; Amanah, Riska Diyanti; Utami, Anindya Noor (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
This study aims to determine the effect of sheep manure and EM4 in composting procces duration using Takakura Methods. The research conducted in laboratory scale using cabbage waste from the nearest market in Cimahi. Another variation are the concentration of sheep manure (10% and 30%) and EM4 (10 ml and 15 ml). There are four samples were done in this study, A (cabbage waste+10% sheep manure +10 ml  EM4), B (cabbage waste+ 30% sheep manure+ 10 ml EM4), C (cabbage waste+10% sheep manure + 15 ml EM4), D(cabbage waste+30% sheep manure+15 ml EM4.) Expectations of this study was produced compost that meets the quality standard of organic fertilizers based on SNI 19-7030-2004 such as C/N ratio, pH, and temperature.The results showed that cabbage waste can be composted after 20 days, its faster than the conventional composting technique. All the samples at the end of composting procces has pH 7, temperature 260C, blackish brown color, and a slight smell of soil. The C/N ratio in each sample is 9,7 (A), 9 (B), 7,43 (C), 8,67 (D). A sample has a value close to the quality standard of organic fertilizers based on SNI 19-7030-2004.